Intensive care. The new technological medicine - Ponce, Pedro (2003)
The intensive care unit is the arena for many of the so-called advances of modern medicine. The introduction of new technologies, the effectiveness and real practical advantages of which have not always been demonstrated beforehand, do however raise some ethical, moral, economic and social issues which are as yet unresolved, and which need to be explained and discussed outside the strictly technical sphere of health professionals.